Spacing of Memory in The Book of My Lives by Aleksandar Hemon* - Durić, Dejan (Poznańskie Studia Slawistyczne, 2019)
The paper examines the memoir The Book of My Lives by Bosnian-American writer Aleksandar Hemon. This non-fiction work explores the author’s childhood in the capital of Bosnia and Herzegovina before the collapse of Yugoslavia, and then his exile experience in Canada and the United States after the outbreak of the war. Through the prism of memory, the book deals with the subject of exiles, uprootedness and efforts to start a new life in a new environment. Being an autobiographical record, The Book of My Lives lends itself to the examination of the issue of exile and memory issues, which is one of the two themes of this paper. The second concerns the understanding of the relationship between memory and space. The paper seeks to show how the spatial dimension is also important for the creation of memory because memories represent an essential factor for the transformation of abstract space into a particular place.